Metaverse and oral and maxillofacial radiology: Where do they meet? - Silva, Thaísa Pinheiro; Andrade-Bortoletto, Maria Fernanda; Freitas, Deborah Queiroz; Oliveira-Santos, Christiano; Takeshita, Wilton Mitsunari [UNESP] (Elsevier, 2024)
Since previous literature regarding the application of the metaverse in education is scarce, the present letter aimed to highlight possible applications, as a complementary tool for the classroom, in the oral and maxillofacial radiology academic experience. The potential risks of the metaverse are also discussed. The metaverse and its possible applications, especially related to enhanced teaching and learning, will become a hot topic in the near future, and therefore, there will be a challenging learning curve before the educator makes the most of these innovative educational tools empowered by deeply interactive virtual reality technology.
Keywords: Augmented reality; Education; Radiology; Virtual reality